School-based HPV Vaccination: The Challenges in a Brazilian Initiative - Julio Cesar Teixeira; Mariana Silva Castro Vianna; Diama Bhadra Vale; Daniella Moretti Arbore; Thais Helena Wilmers Perini; Tulio Jose Tomass Couto; Jose Pedroso Neto; Luiz Carlos Zeferino (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective The present study assesses the implementation and the impact after 2 years of a school-based human papillomavirus (HPV) vaccination program in a Brazilian city. Methods A prospective study assessing the implementation of the program, offering quadrivalent HPV vaccine in two annual doses to girls and boys aged from 9 to 10 years old. The program was started in the city of Indaiatuba, state of São Paulo, Brazil, in 2018, and had authorization from the National Immunization Program. The number of HPV vaccine first doses applied and the coverage in 2018 was calculated and compared to the year 2017. There were described events that have influenced the results. Results The program invited 4,878 children through schools (87.1% of the target population), and 7.5% refused vaccination. Several concurrent events required or competed for health professionals of the vaccination teams. The coverage of the first dose (between 9 and 10 years old) was 16.1% in 2017 and increased to 50.5% in 2018 (p < 0.0001). The first dose in all ages increased 78% in 2018 compared with 2017 (6,636/3,733). Competing demands over the program continued in 2019, and the first dose coverage dropped (26.9%). For 2020, a municipal law instituted school-based vaccination and the creation of dedicated teams for vaccination, and these strategies are waiting to be tested. Conclusion School-based annual HPV vaccination in children between 9 and 10 years old was feasible and increased vaccination coverage, regardless of gender, although the program was vulnerable to competing events.